ASSESSING THE SAFETY OF EARLY DIURETIC ADMINISTRATION IN DYSPNEA PATIENTS WITHOUT A FINAL DIAGNOSIS OF ACUTE HEART FAILURE: AN OBSERVATIONAL STUDY. - Kumar, Santosh; Ankad , Vishwanath; Kumar, Santosh (Student’s Journal of Health Research Africa, 2024)
Background Dyspnea is a frequent and distressing symptom leading to emergency department (ED) visits, often associated with various cardiopulmonary conditions. Diuretics are commonly used in the early management of dyspnea, particularly when acute heart failure (AHF) is suspected. This study investigated the safety of early diuretic administration in dyspnea individuals who are not finally detected with AHF, focusing on thirty-day mortality and readmission rates. Methods A prospective observational study involved 180 dyspnea patients from the BASEL-V registries. Patients were allotted into two groups: those who received diuretics at the ED (n=90) and those who did not (n=90). Thirty-day readmission was the secondary endpoint, while thirty-day mortality was the primary one. T-tests, chi-square testing, Wilcoxon rank-sum tests, and multiple imputations for missing data were used to evaluate the data. Results The study involved 180 patients, with a mean age of 65 ± 12 years in the treated group and 66 ± 13 years in the untreated group. 61.1% of the treated group and 58.9% of the untreated group were male. The groups had similar rates of hypertension (treated: 50%, untreated: 46.7%), diabetes (33.3%, untreated: 35.6%), and chronic renal disease (22.2%). The treatment group had 11.1% 30-day mortality and the untreated group 8.9% (p = 0.62). The treatment group had 22.2% 30-day readmissions and the untreated group 20% (p = 0.70). Baseline characteristics were similar between groups. Conclusion Early diuretic administration in dyspnea individuals without a final diagnosis of AHF does not significantly impact thirty-day mortality or readmission rates. The practice appears to be safe in this patient population. Recommendations Larger sample sizes and longer follow-up times are required for future research to validate these results and offer more definite recommendations on the use of diuretics in patients with dyspnea who do not have AHF.